Detection and substitution-pattern determination of guanidines - Corral, Renée Antonio (1976)
The guanidine function can be detected and its substitution pattern determined taking into account the1H-NMR signals of the N−H and N−C−H groups. Satisfactory results were obtained with mono-to penta-substituted guanidines (as picrate salts).